Analysis of Potential Deviations in the Village Fund Supervision Chain - Poeh, Melda Mariana; Gah, Tiffany N.P. (Borong Newinera Publisher, 2026)
The Village Fund Program represents a key policy initiative of the Indonesian government aimed at accelerating rural development and enhancing community welfare. Despite its strategic importance, its implementation continues to face oversight challenges that create opportunities for irregularities, as observed in Manggarai Regency, East Nusa Tenggara. This study seeks to examine the implementation of the Village Fund oversight system, identify potential points of deviation within the control chain, and analyze the implications of weak supervision on accountability.This research adopts a descriptive qualitative approach using a case study method. The study was conducted in four villages in Satar Mese District, namely Paka, Papang, Lolang, and Umung. Data were collected through in-depth interviews, observation, and documentation involving village heads, officials, BPD members, facilitators, community leaders, and beneficiaries. Data analysis followed thematic procedures, including data reduction, presentation, and conclusion drawing, supported by source and method triangulation to ensure validity. The findings reveal that the oversight system remains suboptimal. Potential irregularities emerge in three dimensions. Procedurally, monitoring and audits are not conducted consistently, with Lolang Village not audited by the Inspectorate between 2019 and 2024. Participatory weaknesses are evident in the limited involvement of the community and BPD. Administratively, documentation and reporting practices remain incomplete. These conditions increase the risk of moral hazard, weaken accountability, and reduce public trust. Grounded in Agency Theory, Fraud Triangle Theory, Good Governance, and public sector deviation perspectives, the study highlights the need to strengthen BPD capacity, enhance officials’ competence, provide internal audit training, and implement periodic external audits to ensure transparent, participatory, and accountable governance.